Imperial power and popular politics : class, resistance and the state in India, c. 1850-1950 - Chandavarkar, Rajnarayan (Cambridge University Press, 1998)
In this series of interconnected essays, Rajnarayan Chandavarkar offers a powerful revisionist analysis of the relationship between class and politics in India between the Mutiny and Independence. Dr Chandavarkar rejects the 'Orientalist' view of Indian social and economic development as exceptional and somehow distinct from that prevailing in capitalist societies elsewhere, and reasserts the critical role of the working classes in shaping the pattern of Indian capitalist development. Sustained in argument and elegant in exposition, these essays represent a major contribution not only to the history of the Indian working classes, but to the history of industrial capitalism and colonialism as a whole. Imperial Power and Popular Politics will be essential reading for all scholars and students of recent political, economic, and social history, social theory, and cultural and colonial studies.--Publisher description.